Performance analysis of orthogonal space-time block code with minimum-selection generalized selection combining receiver over rayleigh fading - Tan, Beng Soon (2013)
An orthogonal space-time block code (OSTBC) with a minimum-selection generalized selection combining (MS-GSC) receiver is proposed and analyzed. The motivation behind the proposition of this scheme is a reduction in complexity and processing power at the receiver, compared with a conventional OSTBC system utilizing the maximum-ratio-combining receiver. In addition, it was shown that the OSTBC/MS-GSC can achieve similar performance, compared with the OSTBC/GSC with reduced processing when the predetermined threshold is optimized. In the analysis of this OSTBC/MS-GSC system over a Rayleigh-fading channel, the moment-generating function is presented, where it can be conveniently used to numerically compute the symbol error rate (SER). The average number of branches that is being selected for processing at the receiver is computed and compared. The analytical results are validated by the simulation results.